The analysis of the civil liability of an insurance broker on the minimum insurance guaranteed sum against liability and the contractual limitation of insurance undertaking liability - Karpińska, Marta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The article is devoted to the analysis of the law regime regulating the professional indemnity insurance issues of insurance intermediaries. The Ordinance of the Finance Minister on the civil liability matters of insurance mediation business, which entered into force 1 July 2015 lays down the civil liability risks for insurance intermediaries pursuing their activity in Poland. The Ordinance, in comparison to its repealed version, takes down the possibility of a contractual limitation of insurance undertaking liability to the criterion of 10% of the redress value and corrects the maximum insurance cover period of (limited to 12 months). It has been found that a wrong transposition of directive No. 2002/92/EC of the European Parliament and of the Council of 9 December 2002 on insurance mediation was the cause of such legislative activity. In addition to making an exhaustive analysis of this amendment, an attempt is made to assess it for the sake of the market share of recipients of insurance services requiring special protection (consumers) and intermediaries (insurance brokers).